Multiparametric analysis of CD8+ T cell compartment phenotype in chronic lymphocytic leukemia reveals a signature associated with progression toward therapy. (3rd April 2019) - Gonnord, Pauline; Costa, Manon; Abreu, Arnaud; Peres, Michael; Ysebaert, Loïc; Gadat, Sébastien; Valitutti, Salvatore
ABSTRACT: CD8 + T cells are frontline defenders against cancer and primary targets of current immunotherapies. In CLL, specific functional alterations have been described in circulating CD8 + T cells, yet a global view of the CD8 + T cell compartment phenotype and of its real impact on disease progression is presently elusive. We developed a multidimensional statistical analysis of CD8 + T cell phenotypic marker expression based on whole blood multi-color flow-cytometry. The analysis comprises both unsupervised statistics (hClust and PCA) and supervised classification methods (Random forest, Adaboost algorithm, Decision tree learning and logistic regression) and allows to cluster patients by comparing multiple phenotypic markers expressed by CD8 + T cells. Our results reveal a global CD8 + T cell phenotypic signature in CLL patients that is significantly modified when compared to healthy donors. We also uncover a CD8 + T cell signature characteristic of patients evolving toward therapy within 6 months after phenotyping. The unbiased, not predetermined and multimodal approach highlights a prominent role of the memory compartment in the prognostic signature. The analysis also reveals that imbalance of the central/effector memory compartment in CD8 + T cells can occur irrespectively of the elapsed time after diagnosis. Taken together our results indicate that, in CLL patients, CD8 + T cell phenotype is imprinted by disease clinical progression and reveal that CD8 + T cell memory compartment alteration is not only a hallmark of CLL disease but also a signature of disease evolution toward the need for therapy.